Growth, Structure, and Spectroscopic Properties of a Disordered Nd:SrLaGaO4 Laser Crystal - Shanshan Fang; Ling Liang; Wei Wang; Yiyang Lin; Yijian Sun; Guoliang Gong; Chaoyang Tu; Herui Wen (Crystals, 2024)
A disordered Nd:SrLaGaO4 (Nd:SLG) laser crystal was successfully grown via the Czochralski (CZ) technique. The crystal structure, refractive index, polarized absorption spectra, and stimulated emission spectra were measured. The spectroscopic properties were studied intensively with the Judd–Ofelt (J-O) theory. The maximum absorption cross sections of π- and σ-polarization at 806 nm were calculated to be 3.73 × 10−20 and 4.05 × 10−20 cm2, corresponding to FWHMs of 6.00 and 6.10 nm, respectively. The maximum emission cross sections of π- and σ-polarization at 1076 nm were 3.97 × 10−20 and 4.12 × 10−20 cm2, with FWHMs of 30.21 and 19.44 nm, respectively. The decay life of the Nd3+:4F3/2 energy level was fitted to be 0.152 ms, and the fluorescence quantum efficiency was 72.72%. The inhomogeneous broadening in spectra benefiting from the disordered structure indicates the Nd:SLG crystal is a promising gain medium for ultrafast laser and tunable laser generations in the near infrared region.